STIMULASI OTAK MENINGKATKAN KEMAMPUAN KOGNITIF LANSIA - Fistra Aryu Brata Dewi, Andria; Induniasih; Lestari, Ratna (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background :  The increasing of  life expectancy is  one of  indicators  of  the successful development. It is showed by increasing the number of elderly and it make the change of physical, psychosocial and cognitive function. The decrease of cognitive function depends on age, education, marital status, physical activities, health history of stroke attack and brain stimulation. The lack of brain stimulation causes the decrease of cognitive ability. Objective : This study aimed to identify the correlation between  brain  stimulation  and  elderly  cognitive ability at Dusun Karangasem Gilangharjo Pandak Bantul Provinsi Daerah Istimewa  Yogyakarta on 2012. Method : The study used cross sectional design. The sample of this research was taken by total sampling method. There were 50 elderly aged 60 ? 69 years old at Dusun Karangasem Gilangharjo Pandak Bantul on 2012. The researcher used univariate and bivariate analysis with Kendall?s tau to analyse the data. Result : It was found that 88% elderly people with high brain stimulation, 8% with moderate brain stimulation, and 4% with a low brain stimulation. The research used MMSE to assess the cognitive ability. It showed 86% elderly people with a normal cognitive ability, 8% with a mild cognitive ability disorder and 6% with severe cognitive ability disorder. The result of  Kendall?s  tau  test  showed  that  the correlation between brain stimulation  and  elderly  cognitive  ability  was  0,000  (p<0,05). Correlation coefficient was 0,915 and that showed significant of correlation. Conclusion and suggestion : There  was  correlation  between  brain  stimulation  and  elderly cognitive ability. The study suggested that elderly people must do brain stimulation to increase their cognitive ability. Keywords : Brain stimulation, elderly cognitive ability